Smart Toolkit for evaluating information products and services - Technical Centre for Agricultural and Rural Cooperation; Inter-American Institute for Cooperation on Agriculture; International Institute for Communication and Development (Technical Centre for Agricultural and Rural Cooperation, 2005)
The Toolkit focuses on the evaluation of information products and services from a learning perspective within the context of agricultural information projects. It is directed at internal evaluation rather than external evaluation.